Rights of nature and public administration: a perspective from the enforcement of the Atrato river and Amazonia judgments - Álvarez-Rondón, Cristian Camilo; Calderón-Moreno, Jessica Paola; Calvo-Caro, Mónica Liliana; Nontoa-Romero, Sebastián Camilo (DIXI, 2024)
This paper arises as a partial result of the research process of the Interdisciplinary Studies Group on Politics, Administration and Rights (geipad), linked to the Escuela Superior de Administración Pública (esap). Its purpose is to analyze the recognition of the rights of nature in the Colombian context and to elucidate how this paradigm has materialized from the compliance with the judicial sentences that recognize both the Atrato River and the Amazon as subjects of rights by the Public Administration at all levels. Likewise, the theory of the biocentric turn of nature as a rights-bearing subject in the framework of the environmental crisis is explored. For this purpose, a qualitative methodological approach and an analytical-critical perspective based on documentary and jurisprudential analysis are used. In conclusion, it can be affirmed, at first, that the Public Administration has achieved insufficient progress in the enforcement of the provisions and that there are great challenges to be faced if this new paradigm is to become a reality.